Impactos generados por la actividad turística en la festividad de la virgen de los dolores y el señor crucificado en el pueblo de virú - Díaz Albarrán, Ana Rosa (2014)
This work is a study and analysis of economic and socio-cultural impacts that have been generated by tourism in the Feast of Our Lady of Sorrows and the Crucified Lord in the town of Virú, Virú district , La Libertad department based on the continued growth of the tourism industry , generating significant revenue for the local community through the development of the activities associated with tourism .This festival is a celebration where religious acts as Masses , novenas , burning fireworks, cuisine, traditional dances of the population and combine the festival does generate interest by visitors who want to be part of this celebration. Also, the economic impacts generated tourism in this festival is reflected in the increasing number of service providers such as: increasing the number of accommodation facilities, food and transportation; increasing the number of guests; increased number of dinners; increased number of passengers Transport; income increase in lodging establishments supply and transportation; and job growth. Further socio-cultural impacts generated by tourism in this party have demonstrated by assessing customs and traditions reflected in the organization of the festival and the positive attitude of the population from fulfilling religious activities issued by the organizers to respect, solidarity, well-being and security is provided . The analytic- synthetic and ethnographic methods were used, and technical interview villagers, tourism service providers; and the inquest of 280 visitors who arrived to the town of Virú.